2001
DOI: 10.1590/s0103-50532001000300003
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal activity of isolated naphthoquinones from Tabebuia and some heterocyclic derivatives: a review from an interdisciplinary study

Abstract: Soc. Bras. Química 0103 -5053 $6.00+0.00 trypanocidal activity in compounds with an imidazole or oxazole ring linked to a naphthopyrane structure. Two naphthoimidazoles presented higher activities (14.5x and 34.8x) than the standard crystal violet. Emphasis is given to the biodiversity of the Brazilian flora as a starting point for the development of an autonomous and creative medicinal chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 16 publications
1
55
0
7
Order By: Relevance
“…As previously discussed for napthaquinones, the lipophylic character introduced by this appendage, as well as the presence of a methoxyl or a phenyl group, are factors that increase the trypanocidal activity. A characteristic of the synthesised naphthoimidazoles is that most of them present aromatic groups containing electron-releasing or electron-withdrawing groups attached to the imidazole ring (Pinto et al 1997b, Neves-Pinto et al 2000, Moura et al 2001. The results suggested that electronic factors related to the phenyl group were not relevant for the biological effect.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 99%
“…As previously discussed for napthaquinones, the lipophylic character introduced by this appendage, as well as the presence of a methoxyl or a phenyl group, are factors that increase the trypanocidal activity. A characteristic of the synthesised naphthoimidazoles is that most of them present aromatic groups containing electron-releasing or electron-withdrawing groups attached to the imidazole ring (Pinto et al 1997b, Neves-Pinto et al 2000, Moura et al 2001. The results suggested that electronic factors related to the phenyl group were not relevant for the biological effect.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 99%
“…Due to the increasing number of reports about the activity of β-lapachone against a wide variety of tumor cells, by inhibition of topoisomerases and induction of apoptosis, Dubin et al (2001) pointed out the potential of clinical applications of this naphthoquinone. Previous studies with b-lapachone showed activity against epimastigotes that was associated to generation of free radicals and inhibition of nucleic acids and protein synthesis (reviewed in De Moura et al 2001). In a study of naphthoquinones isolated from Tabebuia, we synthesized 50 heterocyclic derivatives.…”
Section: Drugs Derived From Natural Sourcesmentioning
confidence: 99%
“…In this context, some natural products obtained from plant extracts or their derivatives, such as quinones, alkaloids, terpenes, and phenolic derivatives, have been proposed for leishmaniasis chemotherapy (9). Recently, we reported evidence that quinone derivatives exhibited promising properties against protozoan parasites, such as Trypanosoma cruzi (10)(11)(12)(13)(14), Leishmania (Viannia) braziliensis, and Leishmania (Leishmania) amazonensis (15). These compounds can be isolated from Bignoniaceae or Verbenaceae trees, and their antimicrobial properties have been well established (16).…”
mentioning
confidence: 99%